“Exodus” in Diaspora and the Homeland: Narrative Technique and a Model for Salvation in Ezra-Nehemiah and Esther - Thambyrajah, Jonathan A. (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2023)
Scholarship has been divided on whether there is any reference to the exodus in the books of Ezra-Nehemiah and Esther. In this article, it is argued that although both books do refer to the exodus, they do not necessarily refer to the book of Exodus. Rather than approaching this problem from the perspective of intertextuality, the article studies the use of exodus motifs as a narratological phenomenon. It compares the way that two texts, one from the diaspora and one from Yehud, use exodus motifs to support their own agendas. In each text, the exodus acts as a model for a type of salvation.